Understanding the well‐being of dentistry students. (1st February 2021) - Stormon, Nicole; Sexton, Christopher; Ford, Pauline J.; Eley, Diann S.
Abstract: Introduction: The transactional model of stress is a framework describing the process for coping with stressful events as a relationship between the individual person and environment. This study aimed to investigate the associations between personality, learning environment and experiences of mental health for a cohort of Australian dentistry students. Materials and methods: Students were invited in 2017 to complete an online questionnaire including the Depression, Anxiety and Stress Scale (DASS‐21), The Dundee Ready Education Environment Measure (DREEM) and Cloninger's Temperament and Character Inventory (TCIR‐140). Students were followed‐up one year later, and generalised estimating equations were used. Results: A total of 219 (response 73.5%) students participated in the study. Two personality profiles of dentistry students were identified. Group 1 were significantly higher in the traits persistence, self‐directedness, cooperativeness and reward dependence, whereas Group 2 were significantly higher in harm avoidance. Students with Group 2 personality had a 3.12 (CI:1.72‐5.65) increased odds of depression compared to Group 1 students. Compared to students with positive perceptions of the learning environment, students with negative perceptions had increased odds of stress (3.48, CI: 1.85‐6.53), depression (2.71, CI: 1.57‐ 4.65) and anxiety (2.59, CI: 1.56‐4.28). Conclusion: Students with personalities high in levels of self‐directedness, cooperativeness and persistence and low in harm avoidance, as found in Group 1, demonstrate high levels of general well‐being. Positive perceptions of the dentistry learning environment were found to be an important influence on students stress. This study highlighted a number of factors important to student well‐being and provides direction for further investigation of interventions aimed at enhancing student well‐being.